Carbonization parameters optimization for the biosorption capacity of Cu2+ by a novel biosorbent from agroindustrial solid waste using response surface methodology - Puari, Aninda T.; Azora, Arti; Rusnam, Rusnam; Yanti, Nika R.; Arlius, Feri; Shukor, M. Y. (Elsevier, 2024)
This research focuses on optimizing the carbonization parameters of Exhausted Kahwa Coffee (EKC) for enhanced biosorption of Cu(II) from aqueous solutions. Utilizing the Box-Behnken design (BBD), the study systematically investigates the combined effects of carbonization temperature, time, and gradient on EKC biochar (EKC-BC) formation, maintaining a constant initial copper concentration. The BBD demonstrates statistical significance through ANOVA testing. The optimized carbonization conditions obtained are at 575.42 °C, 2.59 hours, and a gradient of 19.52 °C/min, yielding a maximum predicted biosorption capacity of 6.62 mg/g. Experimental values for Cu2+ removal rate and adsorption capacity confirm the model's accuracy, with a 2 deviation from predictions. Response surface methodology effectively enhances the preparation conditions of EKC-BC, leading to improved biosorption capacity. Copper biosorption aligns well with a linearly transformed Langmuir isotherm model, while the pseudo-second-order kinetic model accurately forecasts the rate constant. Instrumental analyses, including scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX), Fourier-transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD), provide insights into the surface structural modification of EKC-BC after adsorption of Cu2+.